Quimiossensibilizantes sintéticos e naturais associados a antifúngicos convencionais frente a Fusarium spp. - Venturini, Tarcieli Pozzebon (2016)
The genus Fusarium is characterized by hyaline filamentous fungi that cause a wide spectrum of infections predominantly in immunocompromised patients. Disseminated fusariosis results in high rates of morbidity and mortality, since it is of difficult prevention and treatment. The remarkable primary resistance to conventional antifungals of this genus requires the search for new therapeutic possibilities. A possible attempt is the combination of antifungals and chemosensitizing agents with different mechanisms of action. This study aimed to evaluate the in vitro susceptibility of Fusarium to conventional antifungal agents (amphotericin B, itraconazole, voriconazole and caspofungin); organoselenium compounds (diphenyl diselenide and ebselen), nonantifungal drugs (amiodarone, doxycycline, moxifloxacin, pentamidine, polymyxin B, tigecycline and tobramycin), and phytocompounds (cinnamaldehyde, carvacrol and thymol), through broth microdilution method (M38-A2, CLSI). The combinations between the antifungal agents and chemosensitizers were assessed through the checkerboard technique. Among the antifungals tested amphotericin B showed greater activity in vitro (0.25-8 μg/ml); followed by voriconazole (1-16 μg/ml), itraconazole (>16 μg/ml) and caspofungin (>32 μg/ml). Diphenyl diselenide (4-32 μg/ml), ebselen (2-8 μg/ml), pentamidine (4-32 μg/ml) and polymyxin B (4-16 μg/ml) also showed antifungal activity against Fusarium spp. Ebselen and diphenyl diselenide presented high rates of synergism in combination with amphotericin B (88% and 72%, respectively) or voriconazole (80% e 64%, respectively). Combinations with nonantifungal drugs have also resulted in synergism, highlighting the following associations (% of synergism): tobramycin + amphotericin B (80%) or voriconazole (76%); polymyxin B + amphotericin B (76%) or voriconazole (64%); pentamidine + amphotericin B (72%) or voriconazole (68%); amiodarone + amphotericin B (64%) or voriconazole (76%); and moxifloxacin + amphotericin B (72%) or voriconazole (60%). Furthermore, the phytocompounds thymol and carvacrol have showed potent chemosensitizer activity in association to caspofungin (96% e 88%, respectively). Among all the tested combinations, no antagonistic interactions were observed. In conclusion, the most relevant combinations deserve a future investigation in vivo experimental models, since these associations suggest new potencial candidates for combined therapy against fusariosis.